The Relationship Between Exclusive Breastfeeding And Baby's Weight - Ahmad, Felni Yawati; Harismayanti, Harismayanti (Jambura Nursing Journal, 2024)
FELNIYAWATI AHMAD, The Relationship between Exclusive Breastfeeding and Increased Baby Weight in the Telaga Health Center. Supervised by HARISMAYANTI as chairman and ANI RETNI as member. Exclusive breastfeeding is giving only breast milk without other food and drink by not giving prelactal food, giving formula milk because the milk is not coming out, stopping breastfeeding because the baby or mother is sick, the mother has to work, and the mother wants to try formula milk. Predisposing factors for failure to provide exclusive breastfeeding include the mother not being facilitated to carry out early breastfeeding initiation (IMD). The aim of this research is to find out the relationship between exclusive breastfeeding and increased baby weight in the Telaga Community Health Center working area. This research uses an analytical survey research design using a cross sectional study research design. Samples were taken using a purposive sampling technique. Sampling was based on certain criteria at the time the research took place. Data collections uses questionnaires and observations. Data analysis used the Chi Square test with a significance level (Î±=0.05). The statistical test obtained a p value=0.000 with Î± < 0.05, so there is a relationship between the increase in weight of babies who are exclusivey breastfed and those who are not exclusively breastfed in the working area of the Telaga Community Health Center.